Analysis of business model and growth of an early-stage company in the e-learning market - Prouza, Kamil; Lukeš, Martin, 1976-; Komrska, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
The aim of this thesis is to analyze a business model of an e-learning company in the Czech Republic whose growth has been rather stagnant and identify ways to accelerate it. An analysis of the business model has been made base on the information provided by the owner. Also, a research of current and prospective customers was conducted using a questionnaire distributed through an online tool. The sample for the current customers consisted of all current customer while the sample for prospective customers consisted of 1 473 contacts in production and manufacturing companies. Based on the results, a set of recommendations have been made for the company. The recommendations, if followed, should accelerate the growth and enable the company to become an important player in the e-learning market.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses